2010
DOI: 10.3109/09638281003734417
|View full text |Cite
|
Sign up to set email alerts
|

Access and perceived need for physical and occupational therapy in chronic arthritis

Abstract: Family physicians are less likely to refer patients with RA to therapy. Only about a quarter of patients with chronic arthritis treated in primary care perceived the need for these services. Efforts to improve arthritis care should address education of physicians and patients regarding the benefits of rehabilitation and there should be efforts to increase therapy resources in order to enhance access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 17 publications
1
25
0
3
Order By: Relevance
“…Treatments for chronic noncancer pain are numerous, often costly, and often associated with a variety of health risks [6-20]. Chronic pain treatments include, but are not limited to, the use of opioid and other analgesic medications [9-11,16,21,22], surgical procedures [19,23], injections [24-26], nerve ablations [15], spinal cord stimulators [20,27], physical and occupational therapies [28], biofeedback [29,30], transcutaneous electrical nerve stimulation (TENS) units [31], psychological interventions [32-41], and comprehensive multidisciplinary pain programs [42-45]. Chronic pain is a complex family of disorders with a wide range of causes and courses (eg, disease, injury), and is frequently maintained or exacerbated by additional psychological, behavioral, social, and environmental factors (eg, stress, depression, sleep dysfunction, physical inactivity, financial stress, legal disability) [14,46-48].…”
Section: Introductionmentioning
confidence: 99%
“…Treatments for chronic noncancer pain are numerous, often costly, and often associated with a variety of health risks [6-20]. Chronic pain treatments include, but are not limited to, the use of opioid and other analgesic medications [9-11,16,21,22], surgical procedures [19,23], injections [24-26], nerve ablations [15], spinal cord stimulators [20,27], physical and occupational therapies [28], biofeedback [29,30], transcutaneous electrical nerve stimulation (TENS) units [31], psychological interventions [32-41], and comprehensive multidisciplinary pain programs [42-45]. Chronic pain is a complex family of disorders with a wide range of causes and courses (eg, disease, injury), and is frequently maintained or exacerbated by additional psychological, behavioral, social, and environmental factors (eg, stress, depression, sleep dysfunction, physical inactivity, financial stress, legal disability) [14,46-48].…”
Section: Introductionmentioning
confidence: 99%
“…Feldman and colleagues, who conducted interviews directly with patients, found that 96% of patients who felt they needed rehabilitation services received these services; however, only 26.1% of their sample perceived a need for rehabilitation services. 20 Our study was based on hypothetical scenarios of patients who were presumably referred to PT and OT because of their physician's assessment of need, yet only 26% were given an appointment within 12 months of referral.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the therapists believed that in many cases physicians do not even initiate a referral because they are well aware that the patient will be unable to access a therapist. 19 People with higher levels of education are also more likely to perceive the need for therapy services, [20][21][22][23][24] which may indicate increased knowledge about potential benefits.…”
Section: Discussionmentioning
confidence: 99%
“…21 A seleção dos métodos de avaliação deve levar em consideração as queixas principais do paciente e sua relevância para o quadro clínico apresentado. 23 A tabela 1 ilustra alguns dos instrumentos de avaliação padronizados que compõem a avaliação terapêutica ocupacional do paciente com AR.…”
Section: Avaliação Em Terapia Ocupacionalunclassified